Bilateral paracentral acute middle maculopathy associated with open mitral valve repair - Humza Sulahria; Ohidul Mojumder; Greggory M. Gahn; Arshad M. Khanani (American Journal of Ophthalmology Case Reports)
Purpose: To disseminate a case study of Paracentral Acute Middle Maculopathy (PAMM) occurring bilaterally following open mitral valve repair. Observations: The patient reported to the clinic initially with severe vision loss in both eyes and abnormal findings on retinal imaging indicative of PAMM. After a follow-up of 4 weeks, the patient showed mild improvement in visual acuity. After a follow-up of 16 weeks, the patient showed significant improvement in visual acuity. Conclusions and Importance: There is currently no treatment for PAMM. This report provides an important case of PAMM occurring after a surgery that is the first bilateral case of its kind. It is crucial to continue researching this topic to further understand PAMM and its possible causes and indications.